Neuroprotective potential of novel CARTp analogs in the hippocampus of THY-Tau22 mouse model of Tau pathology - Charvát, Vilém; Vaculová, Petra; Železná, Blanka; Maletínská, Lenka; Pačesová, Andrea (Neuropharmacology, 2025)
Anorexigenic neuropeptides have shown a remarkable potential in the treatment of neurodegenerative disorders, such as Alzheimer's disease (AD). One of the strong anorexigenic neuropeptides is called cocaine- and amphetamine-regulated transcript peptide (CARTp), which is the third most abundant transcript in the hypothalamus. Previously, we introduced a novel palmitoylated analog of 2-SS-CART(61-102), a specific analog of natural CART(61-102) with two disulfide bridges, with anorexigenic and neuroprotective properties. This study explores the impact of 2-SS-CART(61-102) and its palmitoylated analog, palm-2-SS-CART(61-102), on the early progression of Tau pathology characteristic of AD, utilizing the THY-Tau22 transgenic mouse model. Chronic subcutaneous treatment with CARTp analogs improved short-term spatial memory in the Y-maze, reduced the number of neurofibrillary tangles (NFT) in the hippocampal CA1 region, and decreased the level of GFAP + astrocytes in the hippocampus of THY-Tau22 mice. Furthermore, treatment with CARTp analogs showed increased levels of synaptic markers in the hippocampus. A beneficial effect on these attributes makes CARTp analogs promising for AD therapy.
Keywords: Animals; myši transgenní; Anorexigenic neuropeptides; hipokampus; astrocyty; tau Proteins; Mice, Transgenic; prostorová paměť; Cocaine- and Amphetamine-Regulated Transcript Protein; Mice; tauopatie; myši; proteiny nervové tkáně; Astrocytes; THY-Tau22 mice; Neurofibrillary Tangles; Nerve Tissue Proteins; Male; neurofibrilární klubka; modely nemocí na zvířatech; Neuroprotective Agents; Alzheimer's disease; CART peptide; Disease Models, Animal; Tauopathies; Hippocampus; Neuroinflammation; Maze Learning; zvířata; mužské pohlaví; Spatial Memory; Mice, Inbred C57BL; kokainem a amfetaminem regulovaný transkript; bludiště - učení; proteiny tau; Tau pathology; myši inbrední C57BL; neuroprotektivní látky